Mechanistic insights into Rho/MRTF inhibition-induced apoptotic events and prevention of drug resistance in melanoma: implications for the involvement of pirin - Foda, Bardees M.; Baker, Annika E.; Joachimiak, Łukasz; Mazur, Marzena; Neubig, Richard R. (Frontiers in Pharmacology, 2025)
AimOvercoming therapy resistance is critical for effective melanoma control. Upregulation of Rho/MRTF signaling in human and mouse melanomas causes resistance to targeted therapies. Inhibition of this pathway by MRTFi, CCG-257081 resensitized resistant melanomas to BRAF and MEK inhibitors. It also prevented the development of resistance to vemurafenib (Vem). Here, we investigate the role of apoptosis and the protein pirin in CCG-257081-mediated suppression of drug resistance.MethodsUsing naïve and resistant mouse YUMMER melanoma cells, we studied the effect of the BRAF inhibitor Vem with or without CCG-257081 on real-time growth and apoptosis (activation of caspase, Propidium iodide (PI) staining, and PARP cleavage). The effects of CCG-257081 on proliferation (Ki67) and caspase-3 activation were assessed in resistant YUMMER_R tumors in vivo. Finally, two CCG-257081 enantiomers were tested for pirin binding, inhibition of the Rho/MRTF-mediated activation of ACTA2 gene expression in fibroblasts, and the prevention of Vem resistance development by YUMMER_P cells.ResultsVem reduced growth of parental but not resistant cells, while CCG-257081 inhibited both. The combination was more effective than Vem alone. CCG-257081, but not Vem, induced activation of caspase-3 and -7 in resistant cells and increased PARP cleavage and PI staining. CCG-257081 reduced proliferation and activated caspase-3 in YUMMER_R melanoma tumors. Both CCG-257081 enantiomers robustly suppressed development of Vem-resistant colonies with the S isomer being more potent (1 μM IC50).ConclusionCCG-257081 appears to target pre-resistant cells and Vem-induced resistant cells through enhanced apoptosis. Inhibition of pirin or the Rho/MRTF pathway can be employed to prevent melanoma resistance.